1995
DOI: 10.1055/s-2007-1006529
|View full text |Cite
|
Sign up to set email alerts
|

Topical Tissue Factor Pathway Inhibitor Improves Free-Flap Survival in a Model Simulating Free-Flap Errors

Abstract: Free flap failure is frequently due to tension, twisting, kinking, or compression of the vascular pedicle after the anastomosis is completed. A rabbit model simulating these errors was used to evaluate the capacity of topically-applied tissue factor pathway inhibitor (TFPI) to prevent microvascular thrombosis. The rabbit ear was isolated on the central artery and vein. The artery was transected, shortened, repaired, and twisted 360 degrees around the vein. Immediately following the anastomosis. TFPI in concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…In this study, the patency rate of the group treated with 10 μg/mL of rhTFPI was 100% versus 56% in the control group 2 days after exposure. This difference was statistically significant, and prior studies investigating TFPI have shown this dose to be effective 11, 12. Of control vessels, 56% remained patent.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In this study, the patency rate of the group treated with 10 μg/mL of rhTFPI was 100% versus 56% in the control group 2 days after exposure. This difference was statistically significant, and prior studies investigating TFPI have shown this dose to be effective 11, 12. Of control vessels, 56% remained patent.…”
Section: Discussionmentioning
confidence: 51%
“…Khouri et al and Ozbeck et al have shown significant differences in arterial patency rates with TFPI in hypertraumatic and avulsion models when compared to other agents 13, 14. These results were reproduced when applied to rabbit models simulating technical errors with free tissue transfers 11. Lantieri et al exposed everted and intimectomized rabbit arteries to rhTFPI at concentrations as little as 10 μg/mL and compared this to cohorts exposed to hirudin, heparin, and controls 12.…”
Section: Discussionmentioning
confidence: 83%
“…by guest www.bloodjournal.org From without systemic anticoagulation. 54,55 However, many prothrombotic vascular lesions are not easily accessible for topical application. Because ANV and ANV-KPI fusions possess the ability to target the PS-exposed membranes of developing thrombi at sites of vascular lesions, it might be possible to inhibit thrombogenesis in situ by bolus injection or prolonged infusion at very low doses without intense systemic anticoagulation, thus minimizing the risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical research has shown that thrombolytic therapy improves survival in acute myocardial-infarction and cerebrovascular-accident patients (3)(4)(5)(6), that heparin improves survival in certain high-risk subpopulations (7), and that chronic low-dose aspirin therapy may decrease the incidence of all such events (8,9). In addition, a number of new antithrombotic modalities, including enhancement of nitric oxide production (10), tissue-factor pathway inhibitors (11), hirudin (7), antibodies to glycoprotein IIb͞IIIa (2,12), and TNK-tissue-type plasminogen activator (tPA; Genentech; ref. 13), have shown great promise in initial studies.…”
mentioning
confidence: 99%